2007
DOI: 10.1007/s00423-007-0172-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sigmoidectomy in Germany—a standardised procedure?

Abstract: Variability of technical details of laparoscopic sigmoidectomy was surprisingly high among German laparoscopic surgeons. This fact should be considered when discussing clinical studies about laparoscopic sigmoidectomy because trocar position, type of minilaparotomy and dissection techniques may very well influence patient outcome after laparoscopic surgery. Therefore, publications of clinical results concerning laparoscopic sigmoid resection should include a precise description of the technical details of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…This did not influence our further findings or interpretation. Although the technique of open and laparoscopic sigmoid resection and associated vascular dissection for diverticular disease has been described in several surgical compendiums, the technique might be more remote from standardization reflected upon outcomes as generally anticipated [21]. This is exemplified by the publication of a recent randomized controlled trial that demonstrated superior patient reported outcomes with preservation of the inferior mesenteric artery [22].…”
Section: Discussionmentioning
confidence: 96%
“…This did not influence our further findings or interpretation. Although the technique of open and laparoscopic sigmoid resection and associated vascular dissection for diverticular disease has been described in several surgical compendiums, the technique might be more remote from standardization reflected upon outcomes as generally anticipated [21]. This is exemplified by the publication of a recent randomized controlled trial that demonstrated superior patient reported outcomes with preservation of the inferior mesenteric artery [22].…”
Section: Discussionmentioning
confidence: 96%
“…In the last decade, numerous variations of surgical details, such as use of Veress needle, number of ports, or use of a handport system, have been reported in the literature and an audit among minimal invasive surgeons from Germany has shown a great variability in technical details of LASR [2]. The aim of publication is to demonstrate the treatment modalities of LASR for sigmoid diverticulitis using a medial to lateral approach that is (with slight modifications) also feasible for sigmoid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Standard der laparoskopischen Sigmaresektion. Umfrage an 292 Mitglieder der Chirurgischen Arbeitsgemeinsachft Minimal-Invasive-Chirurgie (CAMIC)[8].…”
unclassified